Diseño de una guía didáctica para la adaptación de cuentos a videojuegos de rol para fomentar los procesos de educación literaria y lectura multimodal en bachillerato general unificado - Rodríguez Torres, Lorena Mireya (2022)
The current work is located in Literary Didactics, it analyzes the contribution of the Role-play Videogame Gamification (RPG) as a methodology strategy for the study of the story of Ecuadorian literature in the Unified General Baccalaureate (UGB) classrooms. The main objective was to design a didactic guide that specifies the adaptation process and the literary study from the mobilization of narratives in the digital format and playability space. The methodology design responds to qualitative research interest, and the proposal of the didactic guide is part of a feasible Project to motivate the processes of literary teaching and multimodal reading in secondary school. In the first part, it analyses the relationship between the narratological structure of the story and the RPG as a transmedia narrative, to establish points of relationship and divergences between both genders. Subsequently, it studies the possibilities of teaching and literary learning through the RPG; it contrasts the educator’s role against the adaptation and multimodal reading tools in the classrooms, and the literary and digital skills are detailed that acquire the learners of GBU with the use of these resources. In the third instance, the process and the object of the literary adaptation are explained through the Ecuadorian story selection of the 20th century. This analysis contributes to explaining the protagonism and the narratological possibilities that possess the RPG tools for literary education. It concludes that both narratives encourage a culture of digital literature, as a curricular technique that facilitates and motivates the literary teaching process. Key words: role play video games, text adaptations, didactic guide, literary education, and reading motivation.